Model Integratif Pembelajaran Tafsir Tematik QS. Al-Hasyr: 2-5 dengan Kondisi Sosial-Ekonomi Masyarakat di Ma’had Baitul Qur’an Malang - Zaky Mubarok; Romelah Romelah (TADHKIRAH: Jurnal Terapan Hukum Islam dan Kajian Filsafat Syariah, 2024)
The learning model is an important element in achieving learning goals. The integrative model of thematic interpretation offers an engaging learning experience that supports students to explore the values of the Qur'an in depth. This study describes the objectives, implementation, and integrative model of learning thematic interpretation of QS. Al-Hasyr verses 2-5 in Ma'had Baitul Qur'an Malang. The research uses a qualitative approach of case study type with data collection techniques through observation, in-depth interviews, and documentation, as well as data validation using triangulation. The data obtained was then analyzed using three techniques, namely pattern matching, making explanations and time series analysis (Yin, 2009). The results of the study show that learning aims to provide a deep understanding of the meaning of verses and their relevance to the social conditions of the community, emphasizing the relevance of the content of verses, the history of the Prophet, and their application in the modern socio-economic context. The learning process is carried out systematically through the opening stages, core activities, and closing with the material of the book of tafsir and Siroh Nabawiyah. The lectures, discussions, and question-and-answer methods are used in a humanistic approach. The combination of the connected model and webbed model creates relevant and applicable learning, with a constructivist approach that encourages learners to actively build knowledge through experience and problem-solving.